Modifiable prognostic factors in uterine fibroid development: a systematic review of literature - Alieke L. Keizer; Annika Semmler; Helen S. Kok; Paul J.M van Kesteren; Judith A.F Huirne; Wouter J.K Hehenkamp (Journal of Obstetrics and Gynaecology)
Background Many risk factors in uterine fibroid development have been identified, but women and their physicians are less aware of the influence of lifestyle on uterine fibroid development. The objective of this systematic review is to investigate and summarize modifiable prognostic factors associated with uterine fibroid development.Methods Pubmed and Embase were searched for relevant articles according to PRISMA guidelines. References from included articles were screened and when relevant also included. Human in vivo studies on modifiable factors in fibroid development were included. Studies on non-modifiable factors and treatment, in vitro studies and animal studies were excluded. 607 articles were screened and 33 articles were included. Two independent investigators collected data from the report.Results The strongest risk factor for fibroid development was a high BMI, while the strongest protective factors were a high fruit and vegetable intake and high vitamin D intake.Conclusion More high-quality studies are necessary to better understand the impact of the abovementioned factors as well as the role they play in the growth of already existing fibroids.